Find the derivate of the expression using the general procedure to find the derivative of a polynomial function. To do it, multiply the term times the exponent of the variable and raise the variable to the original exponent minus 1:
![\begin{gathered} f(x)=x^2-4x+3 \\ f^(\prime)(x)=2x^(2-1)-4x^(1-1)-0\cdot3 \\ f^(\prime)(x)=2x-4 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/high-school/n607k3nqnxudoze6m5lvemo5bgpdculmbu.png)
Now that we have the expression for the derivative of the function, evaluate it at the value of x that is in the question statement, which is 1:
![f^(\prime)(1)=2(1)-4=2-4=-2](https://img.qammunity.org/2023/formulas/mathematics/high-school/d55wyvzslfgntw2kw2e2qa9zuo1k14dlen.png)
The derivative of the function is -2 at x=1.